ANALISA PROYEK SISTEM INFROMASI ELEKTRONIK KOPERASI DESA SEBAGAI SARANA PENGEMBANGAN PEREKONOMIAN DESA - imad aqil, imad aqil (JUSS (Jurnal Sains dan Sistem Informasi), 2025)
In this digital era, the use of information technology and internet technology cannot be separated from economic problems. Starting from the current village economy that is not good, there has been a price hike in the market, but not at the purchase price, the absence of a proper selling platform. The purpose of this research is to determine user or user satisfaction with the Village Cooperative Electronic application, to find out about the advantages and disadvantages of this Village Cooperative Electronic application and to know the effects of changes that will occur with the existence of this Electronic Cooperative Desai application.